Hilus Cell Hyperplasia of Fallopian Tubes: A Rare and Incidental Finding with Uterine Leiomyomas - Ansari, IA; Prakash, G; K, R; V, E; Bhat, S (Kathmandu University Medical Journal, 2015)
Hilus cells are ovarian counterpart of testicular leydig cells seen at hilar region of ovary. We present an interesting case of hilus cell hyperplasia in fallopian tube associated with multiple leiomyomata of uterus in a postmenopausal woman. To our knowledge very few cases reported the existence of hilus cells outside the ovary. We received a specimen of hysterectomy with bilateral salpingo-oopherectomy. On gross examination both the tubes showed multiple small yellowish nodules. Microscopic examination showed aggregation of hilus cells beneath a normal tubal epithelium. Hilus cell hyperplasia was not seen in the ovaries. On immunohistochemistry, hilus cell showed positivity for vimentin and calretinin. Co-existence of hilus cell hyperplasia of fallopian tube and leiomyoma is very rare and may be subjected to further research. Kathmandu University Medical Journal Vol.12(1) 2014: 64-66